386 Patient-reported outcomes (PROS) in the garnet trial in patients (PTS) with advanced or recurrent mismatch repair deficient/microsatelite instability-high (DMMR/MSI-H) endometrial cancer (EC) treated with dostarlimab. (4th December 2020) - Kristeleit, Rebecca; Mathews, Cara; Redondo, Andrés; Huang, Joice; Eliason, Laurie; Im, Ellie; Brown, Jubilee
Abstract : Introduction/Background: PROs enable direct measurement of the experiences of pts with cancer related to an intervention. Regulators increasingly use PROs to inform the risks and benefits of new drug candidates, focusing on 3 core concepts: physical functioning (PF), disease-related symptoms (DRS), and symptomatic adverse events (AEs). Dostarlimab is an investigational anti–programmed death-1 monoclonal antibody that has shown activity in pts with advanced dMMR EC (objective response rate, 42%; disease control rate, 58%) and an acceptable safety profile. Here, we report on PROs in pts treated with dostarlimab in the single-arm GARNET trial. Methodology: Pts with recurrent or advanced dMMR/MSI-H EC that progressed on a platinum regimen received 500 mg Q3W*4 of dostarlimab, then 1000 mg Q6W until disease progression or discontinuation (DC). PRO assessment, an exploratory endpoint, was measured using the EORTC-QLQ-C30. PROs were collected at baseline (BL), each dose cycle, and after DC. For PF and DRS (pain and fatigue), we conducted multi-item descriptive analyses, including change from BL. For symptomatic AEs and tolerability (nausea, vomiting, constipation, diarrhoea, tiredness/fatigue), we conducted item-level analyses to understand response distribution and change in response categories from BL: improved, stable, and 1-, 2-, or 3-category worsening. Results: PRO data were available for 66/104 pts who received ≥1 dose of dostarlimab. Questionnaire compliance was consistent across domains, ranging from 100% at BL to 45% at cycle 7. Pain, fatigue, and PF were maintained above BL starting at cycles 1, 3, and 4, respectively. Symptomatic AEs were experienced by a minority of pts, with <25% and <6% of pts having 1- or ≥2-category worsening, respectively. Improved scores were reported by 6% to 37% of pts. Conclusions: PROs from the GARNET trial showed that dostarlimab was generally well tolerated and disease-related symptoms were improved or maintained while on treatment. These data, along with the efficacy and safety profile of dostarlimab, support use of dostarlimab in pts with dMMR/MSI-H advanced EC. Disclosures: Clinical trial registration: NCT02715284 Funding: GlaxoSmithKline, Waltham, MA, USA Encore statement: This data is presented on behalf of the original authors with their permission. Presented at European Society for Medical Oncology (ESMO) annual meeting, September 19–21, 2020, Virtual. Dr. Kristeleit reports personal fees from Tesaro. Dr. Mathews reports institutional grants from Tesaro. Dr. Redondo reports institutional research funding from PharmaMar, Roche, and Eisai; and advisory roles at PharmaMar, AstraZeneca, Tesaro, Roche, and Eisai. Dr. Brown reports honoraria from Olympus; consulting or advisory role at Caris, Tesaro, Clovis, AstraZeneca, and Genentech; and speakers' bureau at Clovis. Drs. Huang, Eliason, and Im are employees of GlaxoSmithKline.